Multi-agent Coordination with Deferred Asynchronous Messaging in a Distributed Coordination Space - Botchkaryov, A. (Видавництво Львівської політехніки, 2022)
A method of multi-agent coordination with deferred asynchronous messaging in a distributed coordination space has been proposed. The method has been based on the concept of multi-agent conditional interaction. The method has used: 1) a distributed coordination space in which agents move; 2) the rules of state transitions for the coordination space nodes depending on the movements of agents; 3) the rules of agents move and state transitions depending on the states of the coordination space nodes; 4) a multi-agent coordination game based on the coordination space and the rules. The coordination space has been implemented based on the distributed shared memory of agents. The rules have been applied by exchanging deferred asynchronous messages between agents through the distributed shared memory. The agent’s decisions about movement in the coordination space and their consequences are interpreted according to the rules in asynchronous messages. Delivery of messages to other agents has been deferred until these agents visit the corresponding nodes of the coordination space. This has ensured: 1) mutual exclusion when agents choose conflicting actions, and 2) resilience of multi-agent coordination to agent failures and loss of coordinating messages. Four multi-agent coordination games have been considered as examples. The issue of fault tolerance of the proposed coordination method has been considered. The simulation results show that the use of the method ensures the resilience of multi-agent coordination to agent failures in the considered coordination games.
Keywords: multi-agent system; multi-agent coordination; coordination space; coordination game